Factors and clinical features associated with failure to achieve a clinical cure among onychomycosis patients with mycological cure - Narachai Julanon (2022)
Treatment of onychomycosis may not always result in a return to normal nail appearance. We retrospectively reviewed the medical records of patients treated for toenail onychomycosis that achieved mycological cure at Siriraj Hospital, Bangkok, Thailand from January 2010 to May 2020 to determine the clinical cure rate and factors associated with failure to achieve a clinical cure. Mycological cure was confirmed by a negative potassium hydroxide (KOH) preparation and negative fungal culture. A clinical cure was defined as at least an 80% improvement in the nail plate without clinical evidence of onychomycosis. Treatment outcomes were assessed by evaluation of toenail photographs by two dermatologists. Demographic data, selected risk factors, oral antifungal treatment types and physical examination of patients with and without clinical cure were recorded and compared. Sixty-seven subjects were included in the study. The mean (±standard deviation (SD)) age of the total study subjects was 65 (±12) years; 54% male. Thirty-eight subjects (57%) had a clinical cure 12 months after initiating treatment. The mean (±SD) age of subjects who failed to have a clinical cure (70 ± 11 years) was significantly (p = 0.011) older than the mean age of subjects who had a clinical cure (62 ± 12 years). Subjects who were significantly less likely to have a clincal cure were those with peripheral vascular disease (p = 0.003), having onychophosis (p = 0.004), having onychauxis (p = 0.004) and having a pincer nail (p = 0.022). In summary, a large proportion of our study subjects failed to have a clinical cure and the factors significantly associated with this were older age, having peripheral vascular disease, onychophosis, onychauxis and pincer nail. We conclude that subjects with these associated factors should be warned prior to treatment that even though they may have mycological cure, they may not have a clinical cure.